Evaluation of mindfulness-based cognitive therapy for life and a cognitive behavioural therapy stress-management workshop to improve healthcare staff stress: study protocol for two randomised controlled trials - Clara Strauss; Jenny Gu; Nikki Pitman; Cavita Chapman; Willem Kuyken; Adrian Whittington (Trials, 2018)
Abstract Background Healthcare workers experience higher levels of work-related stress and higher rates of sickness absence than workers in other sectors. Psychological approaches have potential in providing healthcare workers with the knowledge and skills to recognise stress and to manage stress effectively. The strongest evidence for effectiveness in reducing stress in the workplace is for stress-management courses based on cognitive behavioural therapy (CBT) principles and mindfulness-based interventions (MBIs). However, research examining effects of these interventions on sickness absence (an objective indicator of stress) and compassion for others (an indicator of patient care) is limited, as is research on brief CBT stress-management courses (which may be more widely accessible) and on MBIs adapted for workplace settings. Methods/design This protocol is for two randomised controlled trials with participant preference between the two trials and 1:1 allocation to intervention or wait-list within the preferred choice. The first trial is examining a one-day CBT stress-management workshop and the second trial an 8-session Mindfulness-Based Cognitive Therapy for Life (MBCT-L) course, with both trials comparing intervention to wait-list. The primary outcome for both trials is stress post-intervention with secondary outcomes being sickness absence, compassion for others, depression symptoms, anxiety symptoms, wellbeing, work-related burnout, self-compassion, presenteeism, and mindfulness (MBCT-L only). Both trials aim to recruit 234 staff working in the National Health Service in the UK. Discussion This trial will examine whether a one-day CBT stress-management workshop and an 8-session MBCT-L course are effective at reducing healthcare staff stress and other mental health outcomes compared to wait-list, and, whether these interventions are effective at reducing sickness absence and presenteeism and at enhancing wellbeing, self-compassion, mindfulness and compassion for others. Findings will help inform approaches offered to reduce healthcare staff stress and other key variables. A note of caution is that individual-level approaches should only be part of the solution to reducing healthcare staff stress within a broader focus on organisational-level interventions and support. Trial registration ISRCTN Registry, ISRCTN11723441. Registered on 16 June 2017. Protocol Version 1: 24 April 2017. Trial Sponsor: Sussex Partnership NHS Foundation Trust (ResearchGovernance@sussexpartnership.nhs.uk).